A theory driven, pragmatic trial implementing changes to routine antenatal care that supports recommended pregnancy weight gain - Susan de Jersey; Taylor Guthrie; Leonie Callaway; Jeanette Tyler; Karen New; Jan Nicholson (BMC, 2022)
Abstract Background Prevention of weight gain outside recommendations is a challenge for health services, with several barriers to best practice care identified. The aim of this pragmatic implementation study with a historical control was to examine the impact of implementing a service wide education program, and antenatal care pregnancy weight gain chart combined with brief advice on women's knowledge of recommended gestational weight gain (GWG), the advice received and actual GWG. Methods The PRECEDE PROCEED Model of Health Program planning guided intervention and evaluation targets and an implementation science approach facilitated service changes. Pregnant women < 22 weeks' gestation attending the antenatal clinic at a metropolitan birthing hospital in Australia were recruited pre (2010, n = 715) and post (2016, n = 478) implementation of service changes. Weight measurements and questionnaires were completed at recruitment and 36 weeks' gestation. Questionnaires assessed advice received from health professionals related to healthy eating, physical activity, GWG, and at recruitment only, pre-pregnancy weight and knowledge of GWG recommendations. Results Women who correctly reported their recommended GWG increased from 34% (pre) to 53% (post) (p < 0.001). Between pre and post implementation, the advice women received from midwives on recommended GWG was significantly improved at both recruitment- and 36-weeks' gestation. For normal weight women there was a reduction in GWG (14.2 ± 5.3 vs 13.3 ± 4.7 kg, p = 0.04) and clinically important reduction in excess GWG between pre and post implementation (31% vs 24%, p = 0.035) which remained significant after adjustment (AOR 0.53 [95%CI 0.29-0.96]) (p = 0.005). Conclusions Service wide changes to routine antenatal care that address identified barriers to supporting recommended GWG are likely to improve the care and advice women receive and prevent excess GWG for normal weight women.